Selective imaging and cancer cell death via pH switchable near-infrared fluorescence and photothermal effects - Zhang, Jingye; Liu, Zining; Lian, Peng; Qian, Jun; Li, Xinwei; Wang, Lu; Fu, Wei; Chen, Liang; Wei, Xunbin; Li, Cong (Chemical science (Cambridge), 2016)
Accurately locating and eradicating sporadically distributed cancer cells whilst minimizing damage to adjacent normal tissues is vital in image-guided tumor ablation. In this work, we developed four heptamethine cyanine based theranostic probes, IR1–4 , that demonstrated unique pH switchable near-infrared (NIR) fluorescence and photothermal efficiency. While their fluorescence quantum yields increased up to 1020-fold upon acidification from pH 7.4 to 2.4, their photothermal efficiencies decreased up to 7.1-fold concomitantly. Theoretical calculations showed that protonation of the probes in an acidic environment increased the orbital energy gaps and reduced the intramolecular charge transfer efficiency, resulting in the conversion of absorbed light energy to NIR fluorescence instead of hyperthermia. Substitutions at the terminal indole of the probes fine-tuned their p K a fluo values to a narrow physiological pH range of 4.0–5.3. IR2 , with a p K a fluo of 4.6, not only specifically illuminated cancer cells by sensing their more acidic lysosomal lumen, but also selectively ablated cancer cells via its maximized photothermal effects in the alkaline mitochondrial matrix. As far as we are aware, these probes not only offer the highest physiological acidity triggered NIR fluorescence enhancement as small molecules, but are also the first to specifically visualize and eradicate cancer cells by sensing their altered pH values in cellular organelles. Considering that a disordered pH in organelle lumen is a common characteristic of cancer cells, these theranostic probes hold the promise to be applied in image-guided tumor ablation over a wide range of tumor subtypes.